South Africa's contested transition to energy democracy : lessons and struggles from the Renewable Energy Independent Power Producer Procurement Programme - Davies, Megan Lynne (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021. Thesis (DAdmin)--Stellenbosch University, 2021. Sustainable devl plan&man